2021
DOI: 10.1101/2021.02.17.431721
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immune characterization and profiles of SARS-CoV-2 infected patients reveals potential host therapeutic targets and SARS-CoV-2 oncogenesis mechanism

Abstract: The spread of SARS-CoV-2 and the increasing mortality rates of COVID-19 create an urgent need for treatments, which are currently lacking. Although vaccines have been approved by the FDA for emergency use in the U.S., patients will continue to require pharmacologic intervention to reduce morbidity and mortality as vaccine availability remains limited. The rise of new variants makes the development of therapeutic strategies even more crucial to combat the current pandemic and future outbreaks. Evidence from sev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…S6E). Consistent with previous studies regarding immune response upon infection, LINC00877 (Razooky et al 2017;Policard et al 2021) was downregulated, and SNHG6 upregulated (Zhao et al 2016;Waickman et al 2019). Interestingly, the most transcriptionally repressed lncRNA was the nuclear enriched abundant transcript 1 (NEAT1) (Figure 3C, H).…”
Section: Cell-type Dynamic Regulation Of Lncrnas Upon Ebov Infectionsupporting
confidence: 90%
“…S6E). Consistent with previous studies regarding immune response upon infection, LINC00877 (Razooky et al 2017;Policard et al 2021) was downregulated, and SNHG6 upregulated (Zhao et al 2016;Waickman et al 2019). Interestingly, the most transcriptionally repressed lncRNA was the nuclear enriched abundant transcript 1 (NEAT1) (Figure 3C, H).…”
Section: Cell-type Dynamic Regulation Of Lncrnas Upon Ebov Infectionsupporting
confidence: 90%
“…As shown in Fig. 5A , pathways enriched among the frequent central genes in activated TopNets are predominantly related to cell cycle, which is an expected response to infection by the host immune system ( 55 ), as well as potentially linking SC2 infection with cancer ( 56 , 57 ). Previous studies have observed that cancer patients are more vulnerable to SC2 infection leading to adverse outcomes, likely due to compromised immune system ( 58 ).…”
Section: Resultsmentioning
confidence: 96%
“…CD8 + T cells CD8 + T cells were markedly reduced but CD8 + /CD4 + T cell ratio was higher in COVID-19-infected patients [25,[56][57][58], which was also evidenced by clonally-expanded CD8 + T cells in the blood and bronchoalveolar lavage using scRNA-seq analysis [42,59,60]. CD8 + T cells highly expressed activation markers, such as CD69, TNFAIP3 and HLA class II genes (HLA-DRA ,HLA-DRB1 , and HLA-DRB5 ) [30,34] (Figure 1).…”
Section: Treg Cellsmentioning
confidence: 99%